Assessment of HIV-associated Neurocognitive Disorders in HAART-naïve Individuals: A Cross-sectional Study - Ravi Krishnegowda; Chaitra Rao; Sumesh Yadav; Konda Sai Kiran (Journal of Clinical and Diagnostic Research)
Introduction: Human Immunodeficiency Virus (HIV)-associated Neurocognitive Disorders (HAND) have emerged as a critical concern in managing HIV infection. HIV-related neurological involvement is frequently linked to cognitive impairment and formal neurocognitive tests conducted on People Living with HIV (PLHIV) yield poor outcomes. Depending on the disease severity, HIV-related neurocognitive impairment can be classified as Asymptomatic Neurocognitive Impairment (ANI), Mild Neurocognitive Disorder (MND) and HIV-associated Dementia (HAD). Aim: To evaluate the cognitive function in Highly Active Anti-retroviral Therapy (HAART) naïve PLHIV using the Modified Mini-mental State Examination (3MS) and to associate their immunological status, as well as to evaluate the prevalence of HAND. Materials and Methods: This cross-sectional study was conducted in the Department of General Medicine hospitals affiliated with Bangalore Medical College and Research Institute, Bengaluru, Karnataka, India, from November 2019 to May 2021. A total of 120 HIV HAART-naïve PLHIV were included. Demographic details and data were collected on co-morbidities, baseline CD4 count, opportunistic diseases and World Health Organisation (WHO) clinical staging. PLHIV were assessed for cognitive function using the 3MS and were staged according to Frascati criteria. The Chi-square test was used for data analysis. Results: Among the 120 cases, the mean age was 41.96±11.01 years, with 77 males, 42 females and one transgender individual. A total of 31 (25.8%) cases had a CD4 count of <100 cells/mm³. The most common opportunistic diseases were oral candidiasis and pulmonary tuberculosis (24.2%) and disseminated tuberculosis (15%). A total of 50 (41.6%) PLHIV with a CD4 count of <250 had a 3MS score of <79. Of the 15 parameters of the 3MS, the maximum decrease from the normal value was seen in similarities (45.85%), mental reversal (43%), read and obey (42.33%), first recall (41.10%) and second recall (40.33%). According to Frascati criteria, the prevalence of ANI was 29%, MND was 35% and HAD was 36%. In people with a lower CD4 count (<100 cells/mm³), 50% had HAD, 17.1% had ANI and 9.3% had MND. There was a significant association between the CD4 count of PLHIV and Frascati classification in the present study (p<0.05). Conclusion: Individuals with higher CD4 counts were found to have lesser neurocognitive impairment. The quality of life of PLHIV can be significantly improved if they are screened and treated early in the course of the disease.